Effect of the Ethnomathematics Approach on Junior High School Students’ Mathematical Metaphorical Thinking Skills - Annur Arafah Sukmadianti; Erpin Evendi; Alfira Mulya Astuti (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study was motivated by the low level of students’ mathematical metaphorical thinking skills, which stem from a learning process that still focuses on conventional methods. Therefore, an ethnomathematics approach is needed to link mathematical concepts with local culture and students’ real-life experiences, making learning more meaningful and easier to understand. This study aims to examine the effect of the ethnomathematics approach on the mathematical metaphorical thinking skills of junior high school students. This study employs a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The sample consists of two classes: an experimental class and a control class, each comprising 21 students. The research instrument consisted of an essay test to measure students’ mathematical metaphorical thinking abilities, which was developed based on indicators of mathematical metaphorical thinking and had undergone validity and reliability testing. In addition to the test, this study also used an observation sheet to observe student activities and the implementation of learning during the application of the ethnomathematics approach. Documentation was used as supporting data in the form of photos and records of learning activities. The data used in this study consisted of quantitative data in the form of test results, as well as supporting qualitative data from observations and documentation. Data analysis was conducted using normality tests, homogeneity tests, and independent samples t-tests. The results showed that the ethnomathematics approach had a significant effect on students’ mathematical metaphorical thinking skills. The average posttest scores of the experimental class were also higher than those of the control class. These findings suggest that the ethnomathematics approach can help students understand abstract mathematical concepts through concrete experiences and local culture, thereby making learning more meaningful.